Theory-guided modeling and empiricism in information systems research - Heinzl, Armin (Springer, 2011)
This editorial book presents twelve contributions from the German "Wirtschaftsinformatik" that exemplify the contemporary approach of theory-guided modeling and empiricism which complements existing approaches. It summarizes recent research which has been presented at major international and national conferences in order to demonstrate the growing importance of this stream of research.